2012
DOI: 10.2217/imt.12.37
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Immunotherapy with Extracts Derived from Actinomycetales on Rats with Spontaneous Obesity and Diabetes

Abstract: Our findings suggest that Type 2 diabetes mellitus in the studied rats is associated with obesity, and that both diabetes and obesity can be prevented or improved by treatment with Actinomycetales immune modulators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…More recently, a number of these species, including Gordonia bronchialis ( G. bronchialis ), Rhodococcus coprophilus and Tsukamurella inchonensis , capable of exerting subtly different adjuvant or immunostimulatory activities in human, veterinary and agricultural medicine have been identified (Tarrés et al . ). For example, published studies with heat‐killed G. bronchialis showed that it could limit parasitaemias in rats challenged with live Trypanosoma cruzi (Fontanella et al .…”
Section: Introductionmentioning
confidence: 97%
“…More recently, a number of these species, including Gordonia bronchialis ( G. bronchialis ), Rhodococcus coprophilus and Tsukamurella inchonensis , capable of exerting subtly different adjuvant or immunostimulatory activities in human, veterinary and agricultural medicine have been identified (Tarrés et al . ). For example, published studies with heat‐killed G. bronchialis showed that it could limit parasitaemias in rats challenged with live Trypanosoma cruzi (Fontanella et al .…”
Section: Introductionmentioning
confidence: 97%
“…About 85% of T1DM patients are diagnosed before the age of 20 and more than 15% of this population are related to adults (30 years old). 2,3 Generally, the DM can lead various organ dysfunctions such as nephropathy, neuropathy, hepatopathy, retinopathy, and sexual failures. 4 One of the most important complications of diabetes is the disturbance in the male reproductive system which will impact more men ahead of and during their reproductive years.…”
Section: Introductionmentioning
confidence: 99%
“…A number of aerobic Actinomycetales species, including Rhodococcus coprophilus, Gordinia bronchialis, T. inchonensis, and closely related mycobacteria are able to exert subtly different adjuvant or immunomodulatory activities when injected as suspensions of killed bacilli (Tarres et al 2012). In animal models, preparations of T. inchonensis have been particularly successful in preventing inflammation of the intima of arteries damaged by a balloon catheter and for use in the prevention and treatment of spontaneous type 2 diabetes mellitus .…”
mentioning
confidence: 99%